Analisis Faktor-Faktor yang Mempengaruhi Tingkat Prestasi Atlet Taekwondo, Catur Tunanetra, dan Sepak Bola: Analysis of Factors Affecting Achievement Level in Taekwondo, Blind Chess, and Football Athletes - Sintha Fransiske Simanungkalit; Chandrayani Simanjorang; Dora Samaria; Margareta Dias Listiyawati; Nurul Amrina Sairah (Universitas Airlangga, 2025)
Background: An athlete's peak performance is not only determined by routine training intensity but is also significantly influenced by a multifactorial set of supporting determinants, including nutritional intake, knowledge, and overall physical condition. Objectives: This study aims to examine the association between physical fitness, protein consumption, nutritional knowledge, and nutritional status with the athletic achievement levels of athletes. Methods: This research employed a quantitative observational analytic method with a cross-sectional design. The population included football, blind chess, and taekwondo athletes selected through a total sampling technique, resulting in 143 respondents. Data were collected via questionnaires, anthropometric measurements, and the bleep test. Normality testing indicated that the data were not normally distributed (p-value<0.05); therefore, the Chi-Square test was employed for bivariate analysis. Results: The majority of respondents were male (85.3%) and regional-level athletes (67.8%). Results showed that 61.0% of athletes possessed good physical fitness, although 60.8% had protein consumption levels below the recommended daily requirement. Approximately 53.1% of respondents had good nutritional knowledge, and 77.2% had a normal nutritional status. Bivariate analysis revealed a significant relationship between athletic achievement and physical fitness (p-value=0.013), protein consumption (p-value<0.001), and nutritional knowledge (p-value=0.008). However, nutritional status showed no significant relationship with athletic achievement (p-value=0.055). Conclusions: Physical fitness, protein consumption, and nutritional knowledge are key determinants significantly associated with athletic achievement. Success is highly dependent on nutritional support, literacy, and optimal physical conditioning.